Reliability and validity of cross-national homicide data: a comparison of UN and WHO data - Andersson, Catrine (International journal of comparative and applied criminal justice, 2018)
Data reliability and validity are methodological concerns in cross-national analyses of crime, but there is little agreement on which source of data provides the most reliable estimates. Moreover, few studies have examined the potential threat to validity posed by unclassified deaths. The current study aims to (1) assess the reliability of cross-national homicide data from the United Nations (UN) and the World Health Organization (WHO); and (2) investigate the impact of unclassified deaths on the validity of WHO data. Findings indicate that UN and WHO homicide rates (n=56) differ in magnitude, but produce similar outcomes. The UN data produce more robust results and statistical models with less error. The WHO data are more stable and reliable over time, and better suited for longitudinal analyses. Analyses drawing on WHO data should not disregard unclassified deaths because their inclusion provides a more accurate estimate of the true number of homicides.